Understanding the Effects of Misinformation on Eyewitness Memory in Older Adults - Chaudhary, Himanshu (Tufts University Tisch Library, 2026)
Thesis (M.S.)--Tufts University, 2026.; Submitted to the Dept. of Psychology.; Advisors: Elizabeth Race, and Ayanna Thomas.; Committee: Elizabeth Race, Ayanna Thomas, and John Bulevich.; Keyword: Cognitive psychology